Biorefining lignocellulose into feed and food: the case of sugarcane and a technology outlook - Paz Cedeno, Fernando Roberto; Petrielli, Gabriel P.; Medeiros, Sergio R. de; Berndt, Alexandre; Hernandes, Thayse A. D.; Bonomi, Antonio; Driemeier, Carlos (Frontiers in Bioengineering and Biotechnology, 2025)
This Perspective explores how new technologies can expand lignocellulose biorefineries to include coproducts for animal feed and microbial protein with potential applications in human food. Using the Brazilian sugarcane industry as a case study, the analysis highlights synergies from the spatial coexistence of sugarcane and livestock, as well as economies of scale and product multiplicity in biorefineries. The technology outlook examines selected biomass pretreatments that can generate pretreated biomass with dual use: reactive intermediate for cellulosic ethanol production and ruminant nutrition. However, reliance on biorefined feed requires rebalancing ruminant diets and enhancing nutritional value. Emerging technologies for microbial protein production from biorefining streams are briefly contextualized, considering the potential addition in the diets of livestock and humans. In conclusion, research and development in this domain can unlock key opportunities to enhance the sustainability of bio-based value chains.